Comparison of urea content in milk, measured in different laboratories - Klopčič, Marija; Pogačar, J.; Hanuš, Oto (Acta Agraria Kaposváriensis, 1999)
Urea content was determined by the analysis of ten milk samples with 2 to 3 successions in each of the 6 laboratories (3 in Slovenia, 3 in Czech Republic). Determination method was different, but the principle of urea determination in these laboratories was based on enzymatic and/or photometric method. The average urea content varied from 2.38 mmolfl in the laboratory E to 3.43 mmol in the laboratory D. The highest standard deviation was found in the laboratory A, and the lowest in the laboratory F. The highest VC percent was noticed in the laboratory E (51.0%) and laboratory A (44.7%). The analysis results for the difference in urea content in milk measured in different laboratories indicated the lowest difference between the laboratories A and C, and the highest between the laboratories D and E. Standard deviation of differences ranged from 0.12 and 0.46. With t-test we examined the differences between laboratories, which were in almost all instances highly statistically significant. We also calculated the correlation coefficients among laboratories, ranging from 0.96 to 0.99, and were highly statistically significant. We determined regression coefficients among these laboratories and with linear regression equation predicted values for each laboratory if a certain trait was measured in any of the other laboratories.